Penerapan Metode Design Thinking dalam Perancangan UI/UX Aplikasi Deteksi Mata Pengemudi - Renaldo, Florence; Irsyad, Hafiz; Hartati, Ery (MDP Student Conference, 2025)
The high rate of accidents experienced by car drivers or other vehicle operators is often caused by drowsy eyes. Therefore, this research was conducted to design a UI/UX for a driver eye detection system using the Design Thinking method, which consists of five stages: empathy, definition, ideation, prototype, and testing. These stages ensure that the application can be optimally used by users. This application is also expected to help users reduce the risk of accidents caused by drowsiness on the road.